Food consumption behaviors among preschool children from ethnic minority groups in child development centers, Chiang Rai, Thailand: A qualitative study - Siwarak Kitchanapaibul; Thapakorn Ruanja; Chomnard Singhan; Khwunta Kirimasthong (Journal of Public Health and Development, 2026)
erm health, growth, and cognitive development. Among ethnic minority groups in northern Thailand, disparities in food access, cultural practices, and parental nutrition knowledge may contribute to inappropriate food consumption patterns. Understanding these behaviors within community childcare settings is essential for designing culturally responsive nutrition interventions. This study aimed to explore food consumption behaviors and their influencing factors among preschool children aged 2–6 years from ethnic minority groups attending child development centers in Chiang Rai Province, Thailand. A qualitative study design was employed. Purposive sampling was used to recruit 30 teachers and caretakers from nine child development centers in Mae Fah Luang District, Chiang Rai Province. Data were collected through nine focus group discussions guided by semi-structured interview questions. Transcripts were analyzed thematically following Braun and Clarke’s six-phase framework. Two major themes emerged from the analysis. Food consumption behaviors included reliance on snacks and milk as the main food source. Food was provided by the centers, which allowed children to engage in selective eating. Factors influencing consumption behaviors included cultural traditions, socioeconomic constraints, and the influence of media and advertising on children’s food preferences. Preschool children from ethnic minority communities exhibited diverse and culturally influenced dietary behaviors. These findings highlight the importance of culturally sensitive nutrition education and participatory, school-based programs involving teachers, caretakers, and media literacy components to foster healthier eating habits among young children.